A Conceptual Overview on Relationship between Employee Attitude towards Training and Organizational Commitment - Mathew, G.A.; Zacharias, S. (Department of Human Resource Management, University of Sri Jayewardenepura, Nugegoda., 2016)
Organizational commitment has evidently emerged as the most predictable and researched construct of the employee’s attachment or loyalty to the organization. Anextremely committed person has the emotion that he is working for himself and not somebody else. Training makes a very significant contribution to the improvement of the organizations human resources. The objective of this study is to examine the relationship between employee attitude towards training and organizational commitment. To meet this purpose, extensive literature review was done. In this study, organizational commitment is defined as certain attitudes towards the organization. This includes employees’ attachment to their organizations, the degree of their willingness to be a member of the organization and their acceptance of and commitment to organizational goals and their desire toattain them. Training variables were identified from literature reviews. A conceptual model was developed based on literature reviews done.
Keywords: Employee Attitude towards Training; Organizational Commitment; Benefits from Training, Support for Training